Rethinking global governance - Weiss, Thomas G. (Thomas George) 1946-; aWilkinson, Rorden 1970- (Polity Press, 2019)
"Once celebrated as an answer to the myriad ills of the post-Cold War era, global governance is now in trouble. Written by two of the leading scholars in the field, Rethinking Global Governance provides an antidote to simplistic usage and an authoritative yet readable attempt to grasp the governance of our globe--past, present, and future"--